Penerapan Model Pembelajaran Problem Based Learning Materi Bentuk Permukaan Bumi Untuk Meningkatkan Hasil Belajar IPAS Kelas V SD Negeri 1 Beluk - Christiananda, FR.; R, Suci Permata; Rahmawati, Isna (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This research analyzes the application of the problem based learning (PBL) learning model in the implementation of the independent curriculum. This research is based on the fact that there are still students who do not understand the material explained due to the inappropriate learning model, so the researcher intends to examine whether the PBL learning model is effectively used in learning science and technology about the surface of the Earth. The PBL learning model is a learning model that makes it a problem for students to explore learning material. Based on the research that the researcher conducted using qualitative descriptive methods with the research subjects were fifth grade students at SD Negeri 1 Beluk. It was found that the implementation of the PBL model was considered effective because students gained good learning experiences through group discussions and game-based quizzes.